Respuesta :

The combined transformation rule of the two given steps is;  (x, y) → (x - 7, y + 11)

What is the Transformation rule?

Transformations simply takes the basic function and transforms it to another function.

The rules of transformation are;

  • f(x) transformed to f(x) + a means that the function will be moved 'a' units upwards.
  • f(x) transformed to f(x) - a means that the function will be moved 'a' units downwards.
  • f(x) transformed to f(x + a) means that the function will be moved 'a' units to the left.
  • f(x) transformed to f(x - a) means that the function will be moved 'a' units to the right

Now, we are given the transformation as;

(x, y) → (x + 1, y + 4) followed by (x, y) → (x - 8, y + 7)

Thus, the combined transformation is;

(x, y) → (x + 1 - 8, y + 4 + 7)

⇒ (x, y) → (x - 7, y + 11)

Read more about Transformation rule at; brainly.com/question/4289712

#SPJ1